Clinical Efficacy of a Spiral CT-Guided Balloon Compression Day-Surgery Operation for the Treatment of Trigeminal Neuralgia - Xu, Bing; Jia, Zi-pu; Ren, Hao; Meng, Lan; Shen, Ying; Wang, Tao; Luo, Fang; Lv, Rui (Frontiers in Neurology, 2022)
Objective This study aimed to investigate the clinical efficacy of a balloon compression day-surgery operation under the guidance of spiral computed tomography (CT) three-dimensional (3D) reconstruction for the treatment of trigeminal neuralgia. Methods The clinical efficacy and related indexes of 380 patients with trigeminal neuralgia treated by a spiral CT-guided balloon compression day-surgery operation in the pain department of Beijing TianTan Hospital, from October 2017 to March 2021, were retrospectively analyzed. Results Five patients failed due to foramen ovale puncture or in placing the balloon; two patients had ineffective results after the operation and re-entered the hospital for secondary balloon compression. The initial effective rate of the operation in the 380 patients was 98.16%. All patients were discharged on the day of the operation, the average operation time was 26.46 ± 12.15 min, and the average interval from the completion of the operation to discharge was 2.67 ± 0.95 h. During the follow-up period (1–41 months), 12 patients had pain recurrence, and a Kaplan–Meier analysis revealed that the cumulative pain-free recurrence survival rate at 41 months after the operation was 80.64%. No complications related to foramen ovale puncture occurred. Conclusion The spiral CT-guided balloon compression day-surgery operation is safe, effective, and worthy of clinical promotion.